Modeling electronic transport mechanisms in metal-manganite memristive interfaces - Gomez Marlasca, F. (2013)
We studied La0.325Pr0.300Ca0.375MnO3-Ag memristive interfaces. We present a pulsing/measuring protocol capable of registering both quasi-static i-v data and non-volatile remnant resistance. This protocol allowed distinguishing two different electronic transport mechanisms coexisting at the memristive interface, namely space charge limited current and thermionic emission limited current. We introduce a 2-element electric model that accounts for the obtained results and allows predicting the quasi-static i-v relation of the interface by means of a simple function of both the applied voltage and the remnant resistance value. Each element of the electric model is associated to one of the electronic transport mechanisms found. This electric model could result useful for developing time-domain simulation models of metal-manganite memristive interfaces.